Design and Psychometric Properties of Male Adolescent Health Needs-Assessment Scale - Elham Zare; Masoumeh Simbar; Zohreh Shahhosseini; Hamid Alavi Majd (Shiraz University of Medical Sciences, 2016)
Background: Given the importance of adolescents' health in establishing health in the newly thriving generation of every society, the first step for adolescents' health promotion is health needs assessment. The present study was, therefore, conducted to design a valid and reliable scale for health needs assessment of male adolescents. Methods: This is an exploratory sequential mixed method study (2014-2015). The qualitative part was performed using content analysis approach and aimed to generate items pool. Data collection was performed by 7 focus group discussions with 51 male adolescents, and 10 semi-structured in-depth interviews with 10 other adolescents. Nine further in-depth interviews were also performed with 9 key informants. Purposive sampling was used and continued until data saturation. In the quantitative part, the designed scale was psychometrically assessed through the examination of the face and content validities using qualitative and quantitative methods and also the construct validity using the exploratory factor analysis along with the tool's internal consistency and stability. Results: The content analysis of the data from the qualitative part led to the extraction of 4 main themes and 103 items, which moved to the quantitative stage. The mean content validity index of the scale was estimated 0.91 and content validity ratio was 0.89. The exploratory factor analysis showed 4 factors for the designed scale (49 items), including physical, psychological, social and sexual health needs. The internal consistency and the stability assessment of the scale showed 0.79 and 0.89, respectively. (P<0.001) Conclusion: According to the psychometric assessment, MAHNAS is a valid and reliable scale compatible with the Iranian culture that can be used in the health needs assessment of male adolescents.